The influence of addition of treated kenaf fibre in the production and properties of fibre reinforced foamed composite - Mahzabin M.S.; Hock L.J.; Hossain M.S.; Kang L.S. (Elsevier Ltd, 2023)
Adhesion; Cements; Computer graphics; Concrete mixtures; Concrete products; Curing; Foamed products; Hemp; Kenaf fibers; Light weight concrete; Reinforcement; Scanning electron microscopy; Sodium hydroxide; Surface morphology; Surface roughness; Testing; Water absorption; Weathering; Accelerated weathering tests; Alkaline treatment; Durability property; Energy dispersive x-ray; Fibre reinforced; Industrial product; Initial surface absorptions; Optimal conditions; Durability